The jet engine. (Wiley, 2015)
"The Jet Engine provides a complete, accessibledescription of the working and underlying principles of the gasturbine. Accessible, non-technical approach explaining the workings of jet engines, for readers of all levels. Full colour diagrams, cutaways and photographs throughout, written by RR specialists in all the respective fields, hugely popular and well-reviewed book, originally published in 2005 under Rolls Royce's own imprint"-- Provided by publisher
Keywords: Rolls-Royce Ltd.; Airplanes -- Turbojet engines.; Airplanes -- Jet propulsion.; Aircraft gas-turbines.; elektronické knihy; electronic books